2020
DOI: 10.5603/fm.a2019.0094
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of vidian canal and its relations with surrounding anatomic structures by using cone-beam computed tomography

Abstract: Background: We identified the vidian canal (VC) in a Turkish subpopulation on cone-beam computed tomography (CBCT) images and explored its anatomic relationships; the canal serves as an anatomic pathway during endonasal surgical approaches. Materials and methods: Coronal and axial CBCT images of 100 patients (50 males and 50 females) were evaluated (slice thickness and interval, 0.5 mm). We measured the length of the VC length, extent of VC pneumatisation into the sphenoid sinus, position of the VC relative to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Although some studies [6,11] have already used CBCT to anatomically characterize PC, they are quite restricted to a specific population and none had been conducted targeting a sample of the South American population, specifically, the Brazilian population. These studies still differ from ours, since they only observed the distances between the PC and SS, not worrying about their characterization regarding the morphology (single or double) and about the anatomical relationship as the SE (intimate relationship, protruded, individualized).…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies [6,11] have already used CBCT to anatomically characterize PC, they are quite restricted to a specific population and none had been conducted targeting a sample of the South American population, specifically, the Brazilian population. These studies still differ from ours, since they only observed the distances between the PC and SS, not worrying about their characterization regarding the morphology (single or double) and about the anatomical relationship as the SE (intimate relationship, protruded, individualized).…”
Section: Discussionmentioning
confidence: 99%